Paraben exposure through drugs in the neonatal intensive care unit: a regional cohort study - Iacobelli, Silvia; Commins, Marie; Lorrain, Simon; Gouyon, Beatrice; Ramful, Duksha; Richard, Magali; Grondin, Anthony; Gouyon, Jean-Bernard; Bonsante, Francesco (Frontiers in Pharmacology, 2023)
Background and Objectives Environmental factors influence the development of very preterm infants (VPI, born at less than 32 weeks of gestation). It is important to identify all potential sources of paraben exposure in these vulnerable infants. We aimed to quantify paraben exposure via drug administration, in a cohort of VPI cared for the in neonatal intensive care units (NICU). Methods A prospective, observational study was carried out over a five-year period, in a regional setting (two NICUs using the same computerized order-entry system). The main outcome was exposure to paraben-containing drugs. Secondary outcomes were: time of the first exposure; daily intake; number of infants exceeding paraben acceptable daily intake (ADI: 0-10 mg/kg/d); duration of exposure, and cumulative dose. Results The cohort consisted of 1315 VPI [BW 1129.9 (± 360.4) g]. Among them, 85.5 % were exposed to paraben-containing drugs. In 40.4% of infants, the first exposure occurred during the second week of life. Mean paraben intake and duration of exposure were respectively of 2.2 (±1.4) mg/kg/d and of 33.1 (±22.3) days. Cumulative paraben intake was of 80.3 (±84.6) mg/kg. ADI was exceeded in 3.5% of exposed infants. Lower GA was associated to higher intake and longer exposure (p<0.0001). The main molecules involved in paraben exposure were: sodium iron feredetate, paracetamol, furosemide, and sodium bicarbonate + sodium alginate. Conclusions Commonly used drugs are potential source of parabens, and ADI can be easily exceeded in VPI cared for in NICUs. Efforts are needed to identify alternative formulations paraben-free for these vulnerable infants.